T cell-mediated immunity to Cowdria ruminantium in mice: the protective role of Lyt-2+ T cells - Du Plessis, J L; Berche, P; Van Gas, L (Onderstepoort journal of veterinary research, 1991)
The inability of athymic nude mice to make a drug-aided recovery from infection with either the Kümm or the Welgevonden stocks of Cowdria ruminantium and their inability to mount an immune response, suggest that immunity in heartwater is cell-mediated. The adoptive transfer of immunity with the spleen cells of mice immune to the Welgevonden stock is supportive evidence. Immune spleen cells depleted of Lyt-2+ T cells are unable to confer resistance to challenge to recipient mice, whereas the depletion of L3T4+ T cells had no effect on the protection conferred by immune spleen cells. This is conclusive evidence that immunity in heartwater is largely cell-mediated. Immune serum, C. ruminantium and complement incubated in the presence of mouse peritoneal macrophages, inhibits the infectivity of the heartwater agent, but not in the absence of macrophages. The decreased resistance to challenge of immune mice treated with gloxazone adds further support to the concept that in heartwater persistence of C. ruminantium in the host is associated with immunity.